The Effect Of Using Animation Videos In English Teaching On Students’ Listening Skills: An Experimental Study At Sma N 10 Batanghari Grade X Academic Year 2016/2017 - Muhammad Muzamir (Indonesian Journal of Education Research (IJoER), 2021)
Purpose of the study: The purpose of this study was to determine the significant effect of using animated videos in teaching on students' listening skills. Methodology: This research used a true experimental design with pre and posttest design. The sample was tested by using pretest-posttest control group designs. There were four classes for tenth grade student there. It was started from X1 to X4. The design of this research was an experimental research. The population of this research was the tenth (X) grade students of SMA N 10 Batanghari, in 2016/2017 of academic year. The totals sample is of tenth graders are 113 students. The classes were taken for experimental and control classes were X3 and X4. In experimental research, we need pre-test and post-test to measure the ability of the students. The data gathered from students’ score in posttest and pretest from control and experimental class. The data were analyzed by using the independent t-test to see the significant effect of using animation videos on students’ listening skills. This research compared to both of experimental class and control class by using media in teaching. The experimental class used some animation videos, while the control class used the conventional way. The formula of T-test. Main Findings: The findings of this study indicate that the use of animated videos has a significant effect in teaching English on students' listening skills at SMA N 10 Batanghari. Novelty/Originality of this study: This study uses animated videos in teaching English to determine the effect on students' listening skills.